2013
DOI: 10.1371/journal.pone.0060357
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Endothelial Progenitor Cell Mobilization and Dysfunctional Bone Marrow Stroma in Diabetes Mellitus

Abstract: BackgroundCirculating Endothelial Progenitor Cell (EPC) levels are reduced in diabetes mellitus. This may be a consequence of impaired mobilization of EPC from the bone marrow. We hypothesized that under diabetic conditions, mobilization of EPC from the bone marrow to the circulation is impaired –at least partly– due to dysfunction of the bone marrow stromal compartment.MethodsDiabetes was induced in mice by streptozotocin injection. Circulating Sca-1+Flk-1+ EPC were characterized and quantified by flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 56 publications
(82 reference statements)
3
47
0
1
Order By: Relevance
“…In addition to the altered cytokine gradient, decreased NO, increased reactive oxygen species, and advanced glycation end products in DM impair this migration. 39,50,52 These pathological processes induced by DM also increase apoptosis and decrease proliferation of EPCs. Both in vitro and in vivo studies have shown that hyperglycemia and its associated lipotoxicity with elevated oxidized low-density lipoprotein increases the senescence or apoptosis of EPCs mediated through multiple different molecular pathways, including interleukin 8, Akt, protein kinase C, and p38 mitogen-activated protein kinase ( Figure 1B).…”
Section: Trafficking and Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the altered cytokine gradient, decreased NO, increased reactive oxygen species, and advanced glycation end products in DM impair this migration. 39,50,52 These pathological processes induced by DM also increase apoptosis and decrease proliferation of EPCs. Both in vitro and in vivo studies have shown that hyperglycemia and its associated lipotoxicity with elevated oxidized low-density lipoprotein increases the senescence or apoptosis of EPCs mediated through multiple different molecular pathways, including interleukin 8, Akt, protein kinase C, and p38 mitogen-activated protein kinase ( Figure 1B).…”
Section: Trafficking and Survivalmentioning
confidence: 99%
“…[49][50][51][52][53] Although these abnormalities might not cause a major defect in hematopoiesis, they are associated with reduced differentiation and release of EPCs. Experimental 50,51 and human studies 54,55 also demonstrate that DM impairs the mobilization of EPCs in response to tissue ischemia or cytokines, such as granulocyte colony-stimulating factor.…”
Section: Differentiation and Mobilizationmentioning
confidence: 99%
“…Additionally, diabetes causes bone marrow microangiopathy and dysfunction in animal models (23), which is thought to play a role in low EPC number and mobilization in diabetic humans (2). In mouse models of diabetes, the mobilization of hematopoietic progenitor cells is impaired due to alterations in the bone marrow stroma (14,38), a finding that corresponds with impaired mobilization of hematopoietic progenitor cells in diabetic humans in response to granulocyte-colony stimulating factor administration (14). The exercise-induced release of EPC mobilizing factors and the "health" of bone marrow warrant further study to determine the causes of impaired EPC mobilization in IGT and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…• In rats, induction of mobilisation of stem cells from the BM to peripheral blood by ischaemia [112,125] and G-CSF [113,124] is impaired in type 1 diabetes.…”
Section: Features Of the Diabetic Bmmentioning
confidence: 99%
“…• In mice, type 1 diabetes alters BM niche function, gene expression and cytokine production [113,[122][123][124].…”
Section: Features Of the Diabetic Bmmentioning
confidence: 99%